Pemanfaatan Kulit Kacang Tanah (Arachis hipogaea L.) sebagai Adsorben Zat Warna Metilen Biru - Nurhasni Nurhasni, M.Si; Reski Mar'af; Hendrawati Hendrawati (Jurnal Kimia Valensi, 2018)
Dye waste is a major problem in controlling environmental impacts. Dyestuff waste is an organic compound that is difficult to decompose, resistant, and toxic. If the waste is discharged into the water, it will cause environmental pollution. Research on the absorption of dyestuff of methylene blue by activated peanut shells has been carried out. The purpose of this study was to determine the adsorption efficiency, adsorption capacity, optimum conditions of dye adsorption including variation of contact time, adsorbent concentration, pH, and dye concentration. Adsorption test is carried out by batch method using a shaker. The adsorbent was then analyzed using FT-IR and SEM instruments. The results showed that, after activating the adsorbent had a better character than before activated. Peanut skin that has been activated with optimum NaOH against methylene blue, optimum conditions for adsorption of methylene blue dyestuff with 60 minutes contact time with alkaline activation adsorbent, optimum adsorbent concentration 1%, 50 ppm dye concentration, adsorbent size <180 μm, pH 9 The adsorption isotherm pattern follows the Freundlich isotherm.